Limitations on freedom of speech related to public health. : A few remarks based on the experience of the Republic of Poland with the SARS-CoV-2 pandemic. - Biłgorajski, Artur; Czarnacki, Kamil (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The SARS-CoV-2 pandemic has undoubtedly become a challenge for all lawmakers around the world - implying, among others, the need to introduce restrictions on freedom of expression due to health protection. Different countries dealt with this challenge in various ways, which was influenced not only by the systems in force in these states, but also by the specific characteristics and conditions of these countries. Hence, the purpose of this study is to answer how did the pandemic affect the legal situation in the Republic of Poland, with particular attention being paid to: 1) statements whose purpose or effect was to make it difficult or impossible for the state to perform the obligations implied by "health protection"; 2) statements substantively contesting the official information policy of the state on pandemic issues; 3) statements of representatives of the authorities, which are a reaction to the expression referred to above in points 1 and 2. Of course, this study - due to the modest volume - does not pretend to be exhaustive. Its purpose is only to outline the title topic and related issues.